2001
DOI: 10.1109/77.919660
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of epitaxial YBCO thin film on single domain YBCO substrate for the development of RF components

Abstract: The current trend of telecommunications has motivated an increasing need for an rfcomponent of threedimensional complex geometry in high-performance devices including tunable receivers, transformers, and inductors. In our previous work we have developed a novel substrateless cavity using single domain YBCO. This cavity resonator has been demonstrated to exhibit a high Q value at the rffrequency. The surface resistance of the single domain YBCO at 77 K has reached a low value of 500 :a, comparable to those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As the surface quality of the substrates, such as roughness, cleanliness and grain boundary grooving, play a significant role for the buffer and the YBCO growth and also may affect the superconducting properties [15,[60][61][62], it was concluded that the substrate surface is not stable for thin film deposition and that 310-St. St. is not a good candidate as a substrate material for buffer layer deposition using the spray pyrolysis technique.…”
Section: Spray Pyrolysis Of Mgo On 310-stainless Steel Substrates Fro...mentioning
confidence: 99%
“…As the surface quality of the substrates, such as roughness, cleanliness and grain boundary grooving, play a significant role for the buffer and the YBCO growth and also may affect the superconducting properties [15,[60][61][62], it was concluded that the substrate surface is not stable for thin film deposition and that 310-St. St. is not a good candidate as a substrate material for buffer layer deposition using the spray pyrolysis technique.…”
Section: Spray Pyrolysis Of Mgo On 310-stainless Steel Substrates Fro...mentioning
confidence: 99%
“…Accordingly, the idea of reacting the BaF 2 with water used in the TFA and e-beam BaF 2 approaches suggests that carbon might be removed by a similar reaction as in the TFA route. In our recent studies, however, using a fluorine-free sol-gel approach involving trimethylacetate salts and proponic acid (TMAP) precursor solution, well textured, epitaxial YBCO thin films were synthesized [16][17][18][19]. The transport critical current density was found to steadily increase as the microstructure was improved in the YBCO thin film prepared by the fluorinefree sol-gel TMAP method.…”
Section: Introductionmentioning
confidence: 99%